Pengaruh Penerapan Metode Iqro’ Terhadap Kelancaran Membaca Al-Qur’an Studi Di Madrasah Ibtidaiyah Rohmaniyah Sukawening Garut - Izzan, Ahmad; Noviana, Sonia (MASAGI : Jurnal Pendidikan Agama Islam, 2022)
Understanding and knowing the Quran and its contents is an obligation for all Muslims. Therefore, learning to read and understanding the rules of its recitation is also mandatory to ensure that the meanings and intentions of the Quranic verses are not altered. The Iqro' method is a Quranic reading method that emphasizes direct reading practice. Hence, the Iqro' method can assist students in improving their Quranic recitation fluency. This study aims to describe: (1) the implementation of the Iqro' method at Madrasah Ibtidaiyah Rohmaniyah Sukawening Garut, (2) the fluency of Quranic reading, and (3) the impact of applying the Iqro' method on the fluency of Quranic reading. Consequently, this research seeks to determine the extent of the relationship between the implementation of the Iqro' method (X) and the fluency of Quranic reading (Y). The method used in this study is inferential quantitative, which involves collecting data or information about the phenomena being investigated. Data collection techniques included distributing questionnaires to 25 respondents, conducting observations, and documentation studies. Data processing was conducted through statistical data analysis. The results show that the application of the Iqro' method scores an average of 40.6, placing it within the 3.01-4.00 interval, categorized as very good. Meanwhile, the fluency of Quranic reading scores an average of 39.84, also within the 3.01-4.00 interval, categorized as very good. Based on statistical tests, there is a 43.76% influence of the application of the Iqro' method on Quranic reading fluency. Other factors affecting Quranic reading fluency, accounting for 56.24%, were not examined in this study. These findings summarize the overall results of the research. Keywords: Implementation, Iqro' Method, Quranic Reading Fluency